The translation of sport science research to the field: A current opinion and overview on the perceptions of practitioners, researchers and coaches - Fullagar, H. H. K.; McCall, A.; Impellizzeri, F. M.; Favero, T.; Coutts, A. J. (Sports Medicine, 2019)
Evidence-based practice (EBP) is the collated integration of practitioner expertise, athlete values and research evidence aimed to optimise the decision-making process surrounding sport performance. Despite the academic interest afforded to sport science research, our knowledge of how this research is applied in elite sport settings is limited. This current opinion examines the existing evidence of the translation of sport science research into the field, with a tailored focus on the current perceptions of practitioners, researchers and coaches. Recent studies show that practitioners and researchers report they ascertain sport science knowledge differently, with coaches preferring personal interactions compared with coaching courses or scientific journals. The limited peer-reviewed research shows that coaches perceive their knowledge is greater in fields such as tactical/technical areas, rather than physical fitness or general conditioning. This likely explains coaches` greater perceived value in research dedicated to technical and tactical expertise, as well as mental training and skill acquisition. Practitioners place a large emphasis on the need for research in physical fitness areas, which is likely due to their occupational focus. There are many perceived barriers of sport science research application, including funding, time, coach/player/staff `buy in` and research questions that may not apply to the setting. We contend that researchers and practitioners may benefit in producing research, ascertaining knowledge and disseminating findings in alternative methods that better align with coaches` needs. In addition, educational strategies that focus on real-world context and promote social interaction between coaches, practitioners, organisational personnel and researchers would likely benefit all stakeholders. Key Points